PEMUNGUTAN PAJAK PENGHASILAN DENGAN SISTEM SELF ASSESMENT BAGI WAJIB PAJAK BADAN - -, Radjijo (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2007)
ABSTRACT Collecting incoming tax with system self assessment until now a days, is not yet reenning well as we hope. Factors that make something can not yet be filled wether it has beew meand in the law members 7 in the year 1984 as the third change by the law number 17 in year 2000 (Article 2 chapter (1) the lettter and the third change needs to change, to be perfect and the skill of excecutive officer as a holder of the service of tax payer. Next it still needs to be made to be perfect administratitveley, the taration is a part of law of administration that has been needed to step bravely for applying by approval of government, it doesn’t mather about the regulation of President. Keywords: Tax payer – self assessment